The church in the shadow of the mosque : Christians and Muslims in the world of Islam - Griffith, Sidney Harrison (Princeton, N.J. : Princeton University Press, 2008)
"The Church in the Shadow of the Mosque is the first book-length discussion in English of the cultural and intellectual life of Christians indigenous to the Islamic world. Sidney Griffith offers an engaging overview of their initial reactions to the religious challenges they faced, the development of a new mode of presenting Christian doctrine as liturgical texts in their own languages gave way to Arabic, the Christian role in the philosophical life of early Baghdad, and the maturing of distinctive Oriental Christian denominations in this context." "Offering a fuller understanding of the rise of Islam in its early years from the perspective of contemporary non-Muslims, this book reminds us that there is much to learn from the works of people who seriously engaged Muslims in their own world so long ago."--BOOK JACKET.
I. "People of the Gospel," "People of the Book": Christians and Christianity in the World of Islam -- II. Apocalypse and the Arabs: The First Christian Responses to the Challenge of Islam -- III. Christian Theology in Arabic: A New Development in Church Life -- IV. The Shape of Christian Theology in Arabic: The Genres and Strategies of Christian Discourse in the World of Islam -- V. Christian Philosophy in Baghdad and Beyond: A Major Partner in the Development of Classical Islamic Intellectual Culture -- VI. What Has Baghdad to Do with Constantinople or Rome?: Oriental Christian Self-Definition in the World of Islam -- VII. Between the Crescent and the Cross: Convivencia, the Clash of Theologies, and Interreligious Dialogue.
Includes bibliographical references (p. [181]-212) and index.
Keywords: Christianity and culture -- Arab countries -- History; Christianity and other religions -- Islam -- History; Islam -- Relations -- Christianity -- History; Islam; Christendom; Arab countries -- Church history; Islamitische wereld